2005
DOI: 10.4049/jimmunol.175.9.5950
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Peptides on the Recognition of HLA Class I Molecules by Human HLA Antibodies

Abstract: MHC class I molecules expressed on cell surfaces are composed of H chain, β2-microglobulin and any of a vast array of peptides. The role of peptide in the recognition of HLA class I by serum HLA Abs is unknown. In this study, the solid-phase assay of a series (n = 11) of HLA-A2-reactive, pregnancy-induced, human mAbs on a panel (n = 12) of recombinant monomeric HLA-A2 molecules, each containing a single peptide, revealed peptide selectivity of the mAbs. The flow cytometry membrane staining intensities on the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…In contrast the allo-determinants recognized by anti-Class I monoclonal antibodies have mapped predominantly to the polymorphic first and/or second external domains of the MHC Class I molecule (14, 38, 39). While alloantibodies and the corresponding BCR can discriminate between peptide-MHC Class I complexes (40, 41) the contribution of the peptide to the ability of the antibody to bind to the peptide Class I complex is relatively subtle. In these studies we used K d tetramers bound to the Plasmodium berghei circumsporozoite peptide 252-260 (SYIPSAEKI) as a proof of principle of the technique; however, it remains to be confirmed experimentally whether and to what degree K d tetramers bound to self-peptides would alter the absolute numbers of K d –specific B cells identified.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast the allo-determinants recognized by anti-Class I monoclonal antibodies have mapped predominantly to the polymorphic first and/or second external domains of the MHC Class I molecule (14, 38, 39). While alloantibodies and the corresponding BCR can discriminate between peptide-MHC Class I complexes (40, 41) the contribution of the peptide to the ability of the antibody to bind to the peptide Class I complex is relatively subtle. In these studies we used K d tetramers bound to the Plasmodium berghei circumsporozoite peptide 252-260 (SYIPSAEKI) as a proof of principle of the technique; however, it remains to be confirmed experimentally whether and to what degree K d tetramers bound to self-peptides would alter the absolute numbers of K d –specific B cells identified.…”
Section: Discussionmentioning
confidence: 99%
“…The structural epitope of 69AA has also contact residues on the HLA‐bound peptide (Figure ). Arend Mulder and colleagues have first demonstrated that certain human monoclonal HLA antibodies are peptide dependent (Mulder et al ., ). One can expect that the alleles of the immunizer and the Luminex panel have different peptide repertoires and that the binding of some antibodies will require contact with certain critical residues on the peptide.…”
Section: Description Of the Hla Epitope Registry Websitementioning
confidence: 97%
“…Peptide residues P5, P6, P8, and P9 were identified as influencing the mAb recognition of HLA-B27 and -A11 molecules (5,13,14), whereas the P1 residue was described as being critical for the binding of 4D12 mAb to HLA-B35/-B51 (15). A more recent study with human mAbs revealed the impact of different peptides on the HLA-A2/peptide complexes and its mAb recognition (16).…”
mentioning
confidence: 99%